Early Menarche and Late Menopause are Associated with An Increased Risk of Breast Cancer: A Cross-sectional Study (Mediscope, 2026)
Background: Breast cancer, a leading malignancy in women, is influenced by hormonal and reproductive factors. Early menarche and late menopause increase breast cancer risk due to prolonged estrogen exposure.Objective: To investigate associations between reproductive factors (early menarche, late menopause) and breast cancer risk.Methods: This cross-sectional study at Dhaka Medical College (June 2023 to May 2024) included 32 breast cancer patients. Data were collected via questionnaires and medical records. Statistical analysis was performed using SPSS version 26. Ethical approval and informed consent were obtained.Results: The study included 32 participants with a mean age of 45.2 ± 10.5 years. Early menarche (≤11 years) was observed in 28.1%, and 56.2% were postmenopausal. A positive family history was reported in 37.5%, with 58.3% having an affected mother. Ductal carcinoma (75.0%) was the most common histological type, and 62.5% were ER-positive. Most cases were diagnosed at Stage II (37.5%) or Stage III (28.1%), emphasizing late detection.Conclusion: This study underscores the role of reproductive factors and family history in breast cancer risk, emphasizing the need for early screening.Mediscope 2026;13(1): 16-21